2013
DOI: 10.1038/srep02273
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Binding of Natural Amphiphiles with Graphene Derivatives

Abstract: Understanding the transformation of graphene derivatives by natural amphiphiles is essential for elucidating the biological and environmental implications of this emerging class of engineered nanomaterials. Using rapid discrete-molecular-dynamics simulations, we examined the binding of graphene and graphene oxide with peptides, fatty acids, and cellulose, and complemented our simulations by experimental studies of Raman spectroscopy, FTIR, and UV-Vis spectrophotometry. Specifically, we established a connection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 44 publications
2
51
0
Order By: Relevance
“…Recent studies have also shown that graphene and graphene oxide exhibit several unique modes of interaction with biomolecules such as nucleic acids, lipids and fatty acids, proteins and peptides as well as sugars (Sanchez et al 2011;Radic et al 2013). The preferential adsorption of single-stranded over doublestranded DNA, interleaf let insertion in the hydrophobic core of lipid bilayers, DNA intercalation in the presence of copper cations, and high cargo carrying capacity for conjugated small molecule drugs, which can be physically adsorbed and reversibly desorbed, has also been reported in the literature (Sanchez et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also shown that graphene and graphene oxide exhibit several unique modes of interaction with biomolecules such as nucleic acids, lipids and fatty acids, proteins and peptides as well as sugars (Sanchez et al 2011;Radic et al 2013). The preferential adsorption of single-stranded over doublestranded DNA, interleaf let insertion in the hydrophobic core of lipid bilayers, DNA intercalation in the presence of copper cations, and high cargo carrying capacity for conjugated small molecule drugs, which can be physically adsorbed and reversibly desorbed, has also been reported in the literature (Sanchez et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…126, 136, 205, 206, 220222 DMD methods use discontinuous instead of continuous potential functions to describe inter-atomic interactions, 223, 224 which improves the computational efficiency by avoiding frequent calculations of acceleration and position updates in the traditional MD approach. Both all-atom 136, 221, 225 and CG 217, 222 DMD methods have developed to model the nano-bio interface.…”
Section: Focusing On Biocorona – a Perspective From Atomistic Simulatmentioning
confidence: 99%
“…Atomistic DMD simulations have recently been applied to elucidate the competitive binding of natural amphiphiles including celluloses, peptides, and lipids with graphene oxide nanosheets (GRO), 220 where lipids and peptides displayed stronger binding to GRO than celluloses. Given differential population of natural amphiphiles in the environments (e.g., cellulose is most populated in algal exudates, followed by peptides and lipids), a Vroman-like competitive binding phenomenon was observed, where the most abundant celluloses bound to GRO first but were later replaced by stronger binding lipids with less abundance (Fig.…”
Section: Focusing On Biocorona – a Perspective From Atomistic Simulatmentioning
confidence: 99%
See 1 more Smart Citation
“…Katoch et al [2012] used a combination of experimental and computational tools to demonstrate the complicated changes in the conformation of a dodecamer peptide in the powder form, in aqueous solution, and during non-covalent interactions with graphene and graphite. Radic et al [2013] studied the binding and conformational changes in cellulose, peptides, and fatty acids using discrete MD simulations. These molecules are representative of the moieties found in the algal exudates that were used in their experimental studies.…”
Section: Introductionmentioning
confidence: 99%